Evolution of the histologic classification of thyroid neoplasms and its impact on clinical management. Issue 3 (March 2018) - Xu, B.; Ghossein, R.
Abstract: The vast majority of low grade follicular cell derived thyroid carcinomas follows an indolent clinical course and is associated with very low mortality. Risk stratification using multiple clinical and pathologic characteristics has become the standard of care to guide appropriate management and avoid overtreatment. Over the past few decades, the field of thyroid pathology has witnessed several major changes that significantly impacted upon patients' care. These are: 1) The reclassification of non-invasive encapsulated follicular variant of papillary thyroid carcinoma as noninvasive follicular thyroid neoplasm with papillary-like nuclear features; 2) the diagnosis of Hurthle cell carcinoma based on the presence of capsular and vascular invasion; 3) a detailed definition of poorly differentiated thyroid carcinoma, taking into consideration mitosis and necrosis; and 4) the emphasis on a detailed pathologic analysis such as the extent of vascular invasion and extrathyroidal extension. This review describes these histological concepts and details the history, rationale, and clinical impacts of such changes. These shifts in the classification and characterization of thyroid carcinoma provided a platform supporting therapy de-escalation. In addition several lessons were learned from these changes especially from the misclassification of the non-invasive encapsulated follicular variant of papillary thyroid carcinoma. We hope that the lessons learned will help better classify tumors in the future whether arising in the thyroid or other organs.